2005
DOI: 10.1007/s11284-004-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal change in the distribution of a stream‐dwelling stonefly nymph reflects oxygen supply and water flow

Abstract: We examined the effects of oxygen availability, which has been viewed as a minor factor in streams, on the seasonal and spatial microhabitat distribution of a stonefly. Surveys were conducted in winter and summer in a mountain stream by collecting stones from the streambed and determining the presence or absence of the insect. At each stone sampling, we also measured physical conditions. The probability of the stonefly presence increased significantly with current velocity in summer, but not in winter. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…Thus, the larvae are likely to experience more severe extremes of temperature and low oxygen in their natural environment. Genkai-Kato et al (2005) reported that the probability of stonefly presence was positively correlated with the current velocity of a stream in summer but not in winter because of relatively low oxygen levels in summer. Therefore, the stream flow-dependent distribution of glossosomatid larvae may be more significant in summer (we performed our survey in winter) because of lower oxygen levels in the water and higher rates of oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the larvae are likely to experience more severe extremes of temperature and low oxygen in their natural environment. Genkai-Kato et al (2005) reported that the probability of stonefly presence was positively correlated with the current velocity of a stream in summer but not in winter because of relatively low oxygen levels in summer. Therefore, the stream flow-dependent distribution of glossosomatid larvae may be more significant in summer (we performed our survey in winter) because of lower oxygen levels in the water and higher rates of oxygen consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the study area is presented by Genkai-Kato et al (2005). Water temperature in the study area ranges from 2°C in winter to 19°C in summer (Miyasaka and Genkai-Kato, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, nymphs of multiple mayfly genera were reported in more exposed positions on cobbles and exhibited abdominal positioning by holding their bodies off the substrate at lowered DO concentrations (Wiley and Kohler, 1980). The presence of a second macroinvertebrate order, Plecoptera, was correlated with velocity magnitude and oxygen renewal rates in summer but not in winter because of the warmer temperature and low DO in summer (Genkai-Kato et al, 2005). Genkai-Kato and colleagues specify that this behavior was not due to an oxygen gradient as DO concentrations did not differ between deep and shallow sampling points in winter or summer (Genkai-Kato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a second macroinvertebrate order, Plecoptera, was correlated with velocity magnitude and oxygen renewal rates in summer but not in winter because of the warmer temperature and low DO in summer (Genkai-Kato et al, 2005). Genkai-Kato and colleagues specify that this behavior was not due to an oxygen gradient as DO concentrations did not differ between deep and shallow sampling points in winter or summer (Genkai-Kato et al, 2005). Rather, given a certain DO concentration, the stonefly moves until it can achieve its necessary critical oxygen supply (DO × current velocity) (Genkai- Kato et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation